Jun is phosphorylated by several protein kinases at the same sites that are modified in serum-stimulated fibroblasts. - Baker, S J (1992)
c-jun is a member of the family of immediate-early genes whose expression is induced by factors such as serum stimulation, phorbol ester, and differentiation signals. Here we show that increased Jun synthesis after serum stimulation is accompanied by a concomitant increase in phosphorylation. Several serine-threonine kinases were evaluated for their ability to phosphorylate Jun in vitro. p34cdc2, protein kinase C, casein kinase II, and pp44mapk phosphorylated Jun efficiently, whereas cyclic AMP-dependent protein kinase and glycogen synthase kinase III did not. The sites phosphorylated by p34cdc2 were similar to those phosphorylated in vivo after serum induction. The major sites of phosphorylation were mapped to serines 63, 73, and 246. Phosphorylation of full-length Jun with several kinases did not affect the DNA-binding activity of Jun homodimers or Fos-Jun heterodimers. Comparison of the DNA binding and in vitro transcription properties of wild-type and mutated proteins containing either alanine or aspartic acid residues in place of Ser-63, -73, and -246 revealed only minor differences among homodimeric complexes and no differences among Fos-Jun heterodimers. Thus, phosphorylation of Jun did not produce a significant change in dimerization, DNA-binding, or in vitro transcription activity. The regulatory role of phosphorylation in the modulation of Jun function is likely to be considerably more complex than previously suggested.